Karakteristik dan Perilaku Perjalanan Masyarakat pada Aktivitas Mandatory dan Non Mandatory di Kota Banda Aceh Berdasarkan Revealed Preference Data - Tjut Rizqi Maysyarah Hadi; Febrina Dian Kurniasari; Michel Kasaf; Alfisyahrin (Universitas Iskandar Muda, 2025)
The city of Banda Aceh is experiencing rapid growth, especially in the transportation sector, as the population and daily mobility of people increase. This condition causes various traffic problems such as congestion, pollution, and safety. The Aceh Provincial Government through the Transportation Agency responded to this by providing the Trans Koetaradja Bus as an alternative to public transportation. This bus carries the concept of BRT-lite without a special lane, with the hope of reducing dependence on private vehicles. Although it is generally accepted, the use of Trans Koetaradja is still low due to limited route access and the absence of feeder transportation. This study aims to analyze the characteristics and travel behavior of Trans Koetaradja users and private vehicles in mandatory and non mandatory activities in Banda Aceh. The research was conducted in a quantitative descriptive manner using the revealed preference method with 400 respondents. The results showed that the majority of respondents were women aged 20–29 years old with a bachelor's education background and status as a student. The most dominant mode of transportation is motorcycles, used almost every day by respondents. The use of Trans Koetaradja is still low, with the majority of respondents only using it less than once a month. The average travel time to the bus stop is 2–4 minutes, and the dominant destination for mandatory activities is work, while for non mandatory activities is recreation. This underscores that the limited use of Trans Koetaradja is mainly due to access constraints, despite the presence of a well-defined potential user segment.